Kebijakan Penetapan Tarif Seksio Sesarea Tanpa Penyulit dengan Metode Activity Based Costing Berdasarkan ICD-9CM pada Jaminan Kesehatan Nasional di Rumah Sakit XY Kabupaten Kudus Tahun 2016 - Widjayanto, Amirati Dwishinta W (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Tariff of the Caesarean Section (CS) in JKN Program is much different with the CS tariff applicable in hospital. Therefore it needs to be done the research of tariff assignment policy of CS without complications with the method of Activity-Based Costing (ABC) based on ICD-9CM in the implementation of JKN Program in XY hospital Kudus.This is an analytical case studies which has three stages. First, the preparation of Clinical Pathway (CP) CS without complications with a descriptive qualitative approach and methods of FGD and Brainstorming in data collection. Second, the implementation of CP and the calculation of unit cost of the CS without complications with the quantitative approach and methods of observation ctivity Based Costing. Third, analysis of the results and follow-up of the internal hospital policy to face JKN program by qualitative approach and FGD method.Research results generate CP CS without complication adn CP handling New Healthy Baby Born through CS without Complication . The calculation results of the CS without complications unit cost class II is Rp5,320,957 and Rp5,484,564 for class I. When added with the services then cost of CS without complications class II become Rp7,485,745. and Rp8,380,564 for class I. This figureis still above the applicable standard price of JKN which Rp5.306.800 for class II and Rp6.191.300 for class I. All this time, the hospital policy on tariff setting the priority component competitors as a consideration factor